Integrating AI in Writing Class; Benefits and Challenges - Salsabila Tazkia Zamzam (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study explores the integration of AI (artificial intelligence) in writing classes such as chatGPT, Quillbot, Google translate, etc. in higher education at KH University. Mukhtar Syafa'at, focusing on their engagement and use of AI in the writing classroom. A survey of 5 students and 1 lecturer revealed a generally positive attitude towards AI in the teaching and learning process. Students realize that AI can help them develop ideas in writing class. However, apart from that, you also need to be very concerned about the challenges of using it. This research is relevant to research from Nazari (2021) The results indicate that AI-powered writing tools can be an effective tool for improving learning and technology adoption through format-based rewrites and annotations for non-native graduate students in English language textbook writing use of AI in writing classes shows that there are several benefits and challenges in its application. Insights from this study can provide input for policy development regarding the integration of AI in the writing classes of English department students. Understanding the benefits and challenges of integrating AI can improve the teaching and learning experience in higher education.